Website-Based Employee Attendance System with QR Code at PT Sigap Jaya Sampoerna - Paelani, Piky; Muhammad Ikhsan Thohir (Edumedia Solution, 2026)
The development of information technology encourages companies to adopt digital systems to improve employee attendance management. PT Sigap Jaya Sampoerna previously relied on a manual attendance process that caused data inaccuracies, slow recapitulation, and limited supervision. This study aims to design and implement a web-based employee attendance system integrated with QR Code technology to improve efficiency and accuracy. The system was developed using the Waterfall method, consisting of requirements analysis, system design, implementation, and testing stages. The system enables QR Code-based attendance recording and real-time monitoring of employee presence. The results show that the proposed system simplifies attendance processes, reduces recording errors, and improves transparency in attendance data management. This study proves that a web-based QR Code attendance system can effectively support digital transformation in employee attendance management in private companies.